From immersion to addiction: Modeling the digital mind of students through social media use - Khatatbeh, Yahya M; Alghadyan, Soliman A (Research Journal in Advanced Humanities, 2026)
BackgroundUniversity students increased social media use has generated concerns about digital addiction and immersive digital experiences. Because gifted individuals are highly cognitively engaged with digital surroundings, this issue is very important.ObjectiveThis study examines university students’ social media use, immersive experience, and digital addiction. It measures social media engagement, immersive digital experience, and internet addiction in the study sample. The study also examines the direct and indirect consequences of social media use on digital addiction, focusing on immersive experience as a mediator. The study examines how academic accomplishment and digital use features including social media time, electronic abilities, device type, and platform type predict immersive experience and digital addiction, Finally, the study will develop and test a structural explanatory model to explain the psychological mechanisms behind university students’ digital addiction, providing empirical evidence to support preventive and educational interventions to promote healthy digital engagement.MethodsThis quantitative cross-sectional survey included 330 university students. Bergen Social Media Engagement and Experiences Scale (Be-SMEE), Immersive Experience Questionnaire (IEQ), and Internet Addiction Test data were obtained. SPSS and JASP were used to analyze direct and indirect relationships between study variables using descriptive statistics, Pearson correlation analysis, structural equation modeling (SEM), and bootstrapped mediation analysis.ResultsIn addition to a moderate to high level of immersive experience, the findings revealed significant levels of involvement on social media platforms and behaviors associated with digital addiction. It was shown that the usage of social media did not have a significant direct effect on digital addiction. On the other hand, immersive experiences revealed a substantial negative effect, which indicated that higher degrees of immersion were related with lower levels of digital addiction. There was a substantial correlation between the ability to use electronic devices and the immersive experience, whereas the amount of time spent on social media was positively associated with digital addiction. One of the findings of the mediation study was that immersive experience had a substantial role in mediating the connection between electronic skills and digital addiction. However, this was not the case for the association between other digital use characteristics and addiction.ConclusionThe results suggest that immersive experience functions as a protective psychological mechanism against digital addiction, particularly among students with higher electronic skills. Enhancing positive immersive engagement and digital competencies may therefore be an effective strategy for reducing problematic internet use among university students.